International Monetary Fund Annual Report 2014 : Financial Statements. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2014)
This companion volume to the International Monetary Fund's Annual Report 2014-From Stabilization to Sustainable Growth contains the audited financial statements that form Appendix VI to the report. The financial statements can also be found, together with Appendixes I through V and other materials, on the Annual Report 2014 web page (www.imf.org/external/pubs/ft/ar/2014/eng).